Jaksa Selaku Eksekutor dalam Putusan Pengadilan Tindak Pidana Pembunuhan - I Wayan Edi Kurniawan; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2020)
Enforcement of the criminal justice system in Indonesia can also be carried out by implementing court decisions that have permanent legal force. The party that has the authority to implement the judge's decision is the prosecutor. In the contents of the criminal decision, the prosecutor's office has the authority to immediately carry out the execution in accordance with the Criminal Procedure Code. This study aims to determine the authority of the prosecutor in carrying out the execution, and to determine the execution mechanism for the crime of murder. This research uses normative methods, statutory approaches, conceptual approaches, primary legal materials, secondary legal materials, tertiary legal materials, document studies, literature studies, internet studies and analysis of legal interpretations, and descriptive analysis. The only executing agency in the State of Indonesia is the Attorney General's Office of the Republic of Indonesia. The meaning of executor is the party who has the authority to carry out court decisions based on the applicable law. The results showed that in carrying out court decisions, the prosecutor's office had duties and functions, one of which was as an executor as well as a general prosecutor. A decision that can be executed is only one that has permanent legal force and there are no more legal remedies. Prosecutors as law enforcement officers in carrying out their duties must be based on the applicable legal rules. Do not let the prosecutor violate rules that are not under their authority. Law enforcement officials who carry out executions must carry out the execution as quickly as possible and no criminal offender is executed late.